Discourse Strategies and the Evocation of Solidarity in Chimamanda Ngozi Adichie’s Novels (2017)
Solidarity within social groups is a prominent thematic preoccupation in contemporary African literary works. Previous studies on Adichie’s three novels: Purple Hibiscus (PH), Half of a Yellow Sun (HOAYS) and AMERiCANAH (AH), have examined textual aspects such as language, context, style, and themes with little attention on discourse strategies as they evoke social solidarity in the novels. This study, therefore, examined discourse strategies in relation to how they evoked social solidarity and textual cohesion with a view to deepening the understanding of the texts. The study adopted M.A.K. Halliday’s model of Systemic Functional Linguistics as framework, complemented with Fairclough’s model of Critical Discourse Analysis and Durkheim’s concept of solidarity. The data consisted of 152 extracts from the three novels: 42 from PH, 61 from HOAYS and 49 from AH. These extracts, selected on the basis of their relevance to the evocation of social solidarity and textual cohesion, were subjected to discourse analysis. Discourse strategies such as referential, perspectivation, intensification and mitigation were the major tools for the construction of social solidarity. The referential strategy, a process of constructing and representing social actors by membership categorisation, was exhibited in the form of nominal groups like ‘‘my brother’’(PH),‘‘our family’’(PH),‘‘my man’’(HOAYS), ‘‘Northerners’’(HOAYS),‘‘Black British’’(AH), ‘‘Non-American Blacks’’(AH), and was used to construct characters’ social identities, with the aim of specifying the nature of their social solidarity. Perspectivation, in terms of the narrative point of view, was realised in the form of personal pronouns (I/we/us/they/them) which were used to articulate characters’ perspectives and commitment to social solidarity. Intensification, which implies explicit expressions of qualifying/modifying the epistemic status of propositions, was realised in the use of modal auxiliary ‘‘will’’. For example, ‘‘we will take care of the baby; we will protect him’’ (PH). Similarly, the expression ‘‘Try and make friends with our African American brothers and sisters in a spirit of true pan- Africanism’’ (AH) was a form of explicit intensification, and signified cross-national solidarity. Mitigation, an implicit reference to social solidarity, was realised in expressions like ‘‘There’s no American nonsense in that house’’ (AH) which showed preference for African over American culture. While these discourse strategies enhance mostly familial and kinship solidarities in PH and HOAYS, cross-national solidarity was realised in AH. Expressions with lexical sense relations such as hyponymy (‘‘Kano/North’’ in HOAYS), and meronymy (‘‘black locals/Black Americans’’ in AH), as well as reiteration and collocation amplified social solidarity and enhanced lexical cohesion in Adichie’s texts. In most cases the use of conjunctions, substitutions, and elliptical structures intensified communication of intentions that augmented social solidarity and reinforced grammatical cohesion. Discourse strategies evoked aspects of social solidarity such as collectivism, cooperation, group loyalty and textual cohesion in Adichie’s novels. These provide insights into meaningful and profound interpretations of Adichie’s works.